2023
DOI: 10.1186/s12711-023-00823-0
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality of genomic information and its impact on genome-wide associations and variant selection for genomic prediction: a simulation study

Abstract: Background Identifying true positive variants in genome-wide associations (GWA) depends on several factors, including the number of genotyped individuals. The limited dimensionality of genomic information may give insights into the optimal number of individuals to be used in GWA. This study investigated different discovery set sizes based on the number of largest eigenvalues explaining a certain proportion of variance in the genomic relationship matrix (G). In addition, we investigated the impa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The new peaks had clear linkage disequilibrium trails, meaning that ssGWAS resolution increases as more genotyped animals are included in the analyses. As previously shown, especially for populations with a small effective population size ( Ne ) and more polygenic traits, increasing the genotype set reduces the estimation error and the shrinkage of SNP effects, which increases the power of discovering significant variants (Lourenco et al, 2017; Jang et al, 2023; Misztal et al, 2023). The benefit of an increase in the genotype set size can also be observed when comparing Approx_GinvAPY with approx_GinvAPY450K.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The new peaks had clear linkage disequilibrium trails, meaning that ssGWAS resolution increases as more genotyped animals are included in the analyses. As previously shown, especially for populations with a small effective population size ( Ne ) and more polygenic traits, increasing the genotype set reduces the estimation error and the shrinkage of SNP effects, which increases the power of discovering significant variants (Lourenco et al, 2017; Jang et al, 2023; Misztal et al, 2023). The benefit of an increase in the genotype set size can also be observed when comparing Approx_GinvAPY with approx_GinvAPY450K.…”
Section: Resultsmentioning
confidence: 99%
“…While evaluating two simulated populations with the same Ne, Misztal et al (2023) observed that increasing the number of individuals contributing with genotypes and phenotypes by three times increased the correct identification of significant SNPs. Similarly, Jang et al (2023) showed that for highly polygenic traits (2000 QTN) with Ne of 20 and a moderate heritability of 0.30, no QTN was accurately identified until a complete genotype set, composed of 30K genotyped animals, was included in the analyses. For livestock populations with even smaller Ne and traits of lower heritability, such as reproduction and fitness traits, QTN identification may be even more challenging, especially when limitations exist on the amount of genomic information used in the estimation process.…”
Section: Resultsmentioning
confidence: 99%
“…They were unsuccessful in estimating these effects accurately from genome-wide association studies, presumably due to linkage disequilibrium. Jang et al (Jang et al, 2023) simulated the process of pre-selection by genomewide association studies, exploring under which conditions large effects can be identified to supplement the SNP chip. They concluded that:…”
Section: The Current State Of Genomic Prediction With Whole-genome Se...mentioning
confidence: 99%
“…In recent years, preselected potential causal variants identified through genome-wide association studies (GWASs) have already been applied in genomic prediction to improve the prediction accuracy for a variety of traits in livestock and poultry [19,20], including pigs [21,22]. In certain instances, this strategy has resulted in improved accuracy of genomic prediction for growth and carcass traits in pigs, with improvements ranging from 0.9 to 46% for multi-breed populations [21][22][23]. However, it should be noted that this strategy did not result in improved prediction accuracy in all cases [21,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…A simulation study indicated that the detection of causal variants explained only 20% of the total genetic variance when using a sample size of 7000 for a GWAS in an effective population size of 20 [23]. Recently, Ros-Freixedes et al [21] used preselected SNPs based on GWAS results for genomic prediction, studying a population of nearly 100,000 pigs from the largest lines with imputed WGS data.…”
Section: Introductionmentioning
confidence: 99%